An Active Pattern Infrastructure for Domain-Specific Languages - Levendovszky, Tihamer; Karsai, Gabor (Electronic Communications of the EASST, 2010)
Tool support for design patterns is a critically importantarea of computer-aided software engineering. With the proliferationof Domain-Specific Modeling Languages (DSMLs), the adaptation of thenotion of design patterns appears to be a promising direction ofresearch. This paper introduces a new approach to DSML patterns,namely, the Active Model Pattern infrastructure. In this framework,not only the traditional insertion of predefined partial models issupported, but interactive, localized design-time manipulation ofmodels. Optionally, the infrastructure can be adapted to handlingtransactional tracing information as well as transactional undo andredo operations. Possible realizations of the framework are alsodiscussed and compared